The Chicano generation : testimonios of the movement - García, Mario T. (University of California Press, 2015)
"This is the story of the historic Chicano Movement in Los Angeles during the late 1960s and 1970s. The Chicano Movement was the largest civil rights and empowerment movement in the history of Mexican Americans in the United States. The movement was led by a new generation of political activists calling themselves Chicanos, a countercultural barrio term. This book is the story of three key activists, Raul Ruiz, Gloria Arellanes, and Rosalio Muñoz, who through oral history related their experiences as movement activist to historian Mario T. García. As first-person autobiographical narratives, these stories put a human face to this profound social movement and provide a life-story perspective as to why these individuals became activists"--Provided by publisher.